PENGARUH PROBIOTIK DADIAH TERHADAP PERBAIKAN SEL HEPATOSIT JARINGAN HATI PADA TIKUS MODEL DIABETES - Rinita Amelia; Nadia Purnama Dewi; Meta Zulyati Oktora; Mhd Nurhuda; Sarah Lativa (Yayasan Nusantara Hasana Berdikari, 2025)
The high incidence of DM causes diabetes to become a health problem. For this reason, other supportive therapies are needed such as the use of probiotics which are known to have antidiabetic effects, high antioxidants and as anti-inflammatory that can improve the structure and function of organs. This study aims to determine the effect of dadiah administration on the histopathological picture of liver hepatocyte cells in diabetic model mice. The research method was an experimental study of male white rats of the wistar strain of white rats, which were divided into control groups and treatment groups. The previous treatment group in Induction became a type 2 diabetes rat model by injecting Streptozotocin (STZ) 45 mg/kgBB intraperitoneally. Dadiah intervention and BAL isolates were administered for 2 months and were analyzed the histopathological picture of rat liver tissue after the intervention and compared with controls. The results of the study showed an improvement in the histopathological structure of the liver in DM rats that experienced damage to liver tissue hepatocyte cells by the administration of dadiah and probiotics (L. Fermentum) at both low dose and high dose (p-value 0.001). The conclusion that dadiah and probiotic dadiah have been shown to be pathologically anatomically beneficial to degenerative and necrotic liver hepatocyte cells in diabetic rat model, due to their antioxidant and anti-inflammatory activity.